Application of analytical hierarchy process in implementation of community forest management permit work plan. Issue 1 (November 2021) - Sitanggang, R F; Rahmawaty; Zaitunah, A
Abstract: Community Forest Utilization Business Permit (CFUBP), is a permit granted to utilize forest resources in forest areas whose main use is intended to empower local communities. This study aims to analyze the priority level of the implementation of the Annual Work Plan (AWP) for CF management in Bina Mangrove Forest Farmers Group (FFG), Sentang Village, Teluk Mengkudu District, Serdang Bedagai District. The research was conducted from January to March 2021 using primary and secondary data. The method used is Analytical Hierarchy Process (AHP) using expert choice software tools. The data collection method is Focus Group Discussion (FGD). From the results of seeding with AHP, the priority for implementing the Annual Work Plan (AWP) for CF management in the Bina Mangrove FFG is the forest utilization criteria with a value of 0.54. The criteria for forest protection or security, development of local wisdom, monitoring and evaluation are next with the same value of 0.14. The criteria for marking the boundaries of the working area or zoning are in the last order with a value of 0.04. The value of inconsistency is 0.08.